Live TikTok Library: Promosi On-Fleek untuk Pengalaman yang Semakin Seru - Pratiwi, Enjela; Delliana, Santi; Wahyu Wasana, Fredi; Kusuma Sari, Erlina (Forum Perpustakaan Perguruan Tinggi Indonesia, 2022)
In the ever-evolving digital era, libraries increasingly face the challenge of remaining relevant and connected to a fast-moving society. To expand reach and increase engagement, libraries are now involving themselves in social media platforms, and one of them is TikTok. Libraries' use of the live TikTok feature is a progressive step in presenting information, promoting collections, and building communities in cyberspace. Live TikTok provides a dynamic platform for librarians to communicate in real-time with patrons. How can this development improve the library's On-Fleek Promotion concept in interacting with today's digital society? The research method used is qualitative with an observational approach. Data was collected through direct observation of library live broadcasts on TikTok, including interactions between librarians and users, the type of content presented, and user responses. Analysis is carried out by detailing the findings that emerge from these interactions. The research results show that TikTok's live feature provides an interactive platform for libraries to communicate directly with followers. Observations reveal that live TikTok is effective in building user engagement, especially through comments, likes, and virtual gifts. Librarians can actively respond to questions, provide book recommendations, and explain library services. By combining qualitative and observational research methods, this study provides an in-depth understanding of the dynamics of interactions in the library's live TikTok environment. The implications of these findings provide guidance for libraries in designing more effective content strategies and enriching user experiences on these social media platforms.